B cell analysis in SARS-CoV-2 versus malaria: Increased frequencies of plasmablasts and atypical memory B cells in COVID-19. Issue 1 (4th December 2020) - Wildner, Nils H; Ahmadi, Parimah; Schulte, Sophia; Brauneck, Franziska; Kohsar, Matin; Lütgehetmann, Marc; Beisel, Claudia; Addo, Marylyn M; Haag, Friedrich; Schulze zur Wiesch, Julian
Abstract: B cells play a central role in antiviral and antiparasitic immunity, not only as producers of antibodies, but also as APCs and mediators of inflammation. In this study, we used 16-color flow cytometry analysis to investigate the frequency, differentiation, and activation status of peripheral B cells of patients with SARS-CoV-2 infection or acute Plasmodium falciparum malaria compared with the healthy individuals. As a main result, we observed an increase of the frequency of (CD27 –, CD21 – ) atypical memory B cells and (CD19 +, CD27 +, CD38 + ) plasmablasts in malaria and COVID-19 patients. Additionally, CD86, PD-1, CXCR3, and CD39 expression was up-regulated, whereas CD73 was down-regulated on plasmablasts of COVID-19 and malaria patients compared with the bulk B cell population. In particular, there was a more pronounced loss of CD73 + B cells in malaria. The frequency of plasmablasts positively correlated with serum levels of CRP, IL-6, and LDH of COVID-19 patients. In the longitudinal course of COVID-19, a rapid normalization of the frequency of atypical memory B cells was observed. The role and function of plasmablasts and atypical memory B cells in COVID-19 and other acute infections remain to be further investigated. The role of B cells as either "driver or passenger" of hyperinflammation during COVID-19 needs to be clarified. Graphical Abstract: Plasmablasts and atypical memory B cells are more frequent in patients with COVID-19 and malaria than in healthy subjects.